Realizing Golden Indonesia: Islamic Education in Developing An Excellent Generation - Nur Iffah Qoyyumillah; Siti Aminah; Nur Kholis; Muhammad Najib; Saeful Anam; Mohd Sadad bin Mahmud (Jurnal At-Tarbiyat: Jurnal Pendidikan Islam, 2025)
Indonesia's vision of becoming a prosperous and globally competitive nation by 2045, referred to as Golden Indonesia, needs the development of an excellent generation equipped with intellectual, ethical, and leadership capacities. This study aims to discuss the contribution of Islamic education to the development of future generations through curriculum development, character formation, and educational policies that meet Indonesia's socio-cultural and economic aspirations. This study, employing qualitative research methods and literature reviews, argues that Islamic education enhances human capital and promotes sustainable development by cultivating moral integrity, innovation, and global competitiveness. The findings suggest that Islamic education is a comprehensive approach to balancing spiritual and intellectual growth, which can significantly contribute to Indonesia's long-term development. This research highlights the need for policy reforms that enhance the quality and inclusivity of Islamic education, preparing a future-ready generation capable of leading Indonesia toward its golden era.